Sarkopenia: Penilaian Kekuatan Otot Lansia dengan Diabetes Mellitus Tipe 2 Berdasarkan Indikator AWGS - Ratmawati, Ratmawati; Enardi, Ori Pertami; Emilia, Emilia (Ghidza: Jurnal Gizi dan Kesehatan, 2025)
The progress in Asia, AWGS (2019) re-establishes that the incidence of sarcopenia can be seen based on decrease in muscle strength. The new diagnosis was "possible sarcopenia" with the aim of early detection for the elderly. Objective: To analyze the muscle strength of elderly with T2DM based on AWGS indicators (age, muscle mass, intake of energy, fat and carbohydrate, physical activity and sedentary activity) in the Air Itam Community Health Center. Method: cross-sectional study involving 90 of elderly people, aged ≥ 55 years. Data was obtained from interviews, measurements of muscle mass and HGS, IPAQ questionnaires, and 1x24 hour food recall. Results: The average muscle strength of elderly with T2DM in the low category was 58.9% (53 people). It means that the elderly had been diagnosed with "possible sarcopenia". The results of statistical test analysis also stated that there was relationship between variables age, muscle mass, intake of energy, fat and carbohydrates, as well as physical activity and sedentary activity with muscle strength in the elderly (p value < 0.05). Conclusion: Elderly with T2DM are diagnosed with "possible sarcopenia" of 58.9%. Recommendation: research nutritional interventions through physical activity and food intake to maintain muscle strength.